Ambulatory blood pressure in children with obstructive sleep apnoea: a community based study. Issue 9 (3rd April 2008) - Li, A M; Au, C T; Sung, R Y T; Ho, C; Ng, P C; Fok, T F; Wing, Y K
Abstract : Background: Childhood obstructive sleep apnoea (OSA) is increasingly being recognised. Its effects on blood pressure (BP) elevation and hypertension are still controversial. Objective: To evaluate the association between OSA and ambulatory BP in children. Methods: Children aged 6–13 years from randomly selected schools were invited to undergo overnight sleep study and ambulatory BP monitoring after completing a validated OSA questionnaire. OSA was diagnosed if the obstructive apnoea–hypopnoea index (AHI) was >1, and normal controls had AHI <1 and snoring <3 nights per week. Children with OSA were subdivided into a mild group (AHI 1–5) and moderate to severe group (AHI >5). Results: 306 subjects had valid sleep and daytime BP data. Children with OSA had significantly higher BP than normal healthy children during both sleep and wakefulness. BP levels increased with the severity of OSA, and children with moderate to severe disease (AHI >5) were at significantly higher risk for nocturnal systolic (OR 3.9 (95% CI 1.4 to 10.5)) and diastolic (OR 3.3 (95% CI 1.4 to 8.1)) hypertension. Multiple linear regression revealed a significant association between oxygen desaturation index and AHI with daytime and nocturnal BP, respectively, independent of obesity. Conclusions: OSA was associated with elevated daytime and nocturnal BP, and is an independent predictor of nocturnal hypertension. This has important clinical implications as childhood elevated BP predicts future cardiovascular risks. Future studies should examine the effect of therapy for OSA on changes in BP.